Unifying Diversities: Early Institutional Formation of the Indonesian National Education System c. December 1949 – August 1950 - Agus Suwignyo (Humaniora, 2012)
This paper explores the unification of the school system in Indonesia from December 1949 to August 1950. The unification of the educational system during this eight-month period reflected the Indonesian state formation in its earliest stage. It was a process of indonesianization in which the Indonesian Republicans in the Yogyakarta administration dominated the arena. State intervention in the teaching of religious courses and the position of the school system for non-Indonesian children were two of the most critical issues. At the same time, centralization of educational policy making was looming. The aim of this paper to examine the early process of the Indonesian state formation in education by making use of the archives disposed at ANRI that so for have been much neglected in the writing of the history of Indonesian education.